The synthesis and spectral characterization of new Cu(II), Ni(II), Co(III), and Zn(II) complexes with Schiff base - Temel, H; Ilhan, S; Sekerci, M; Ziyadanogullari, R (Taylor & Francis Inc, 2002)
Cu(II), Ni(II), Co(III) and Zn(II) complexes with Schiff base have been prepared. Ligand is derived from condensation of 1,2-bis(p-aminophenoxy)ethane and 2-hydroxynaphthalin-1-carbaldehyde. The complexes have been characterized by elemental analyses, Lambda(M), IR, UV-VIS, H-1 NMR, C-13 NMR and magnetic measurements. The ligand is coordinated to the central metal as a tetradentade ONNO ligand. The four bonding sites are the azomethine nitrogen and aldehydic-OH groups.
Keywords: Schiff bases; transition metals